2010
DOI: 10.3109/07388551.2010.505909
|View full text |Cite
|
Sign up to set email alerts
|

Operating bioreactors for microbial exopolysaccharide production

Abstract: There is considerable interest in exploiting the novel physical and biological properties of microbial exopolysaccharides in industry and medicine. For economic and scientific reasons, large scale production under carefully monitored and controlled conditions is required. Producing exopolysaccharides in industrial fermenters poses several complex bioengineering and microbiological challenges relating primarily to the very high viscosities of such culture media, which are often exacerbated by the producing orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 100 publications
1
28
0
2
Order By: Relevance
“…Therefore, in order to obtain high yields of a consistent polymer, it becomes essential to standardize a large-scale production process with a given strain under controlled conditions (Fariña et al, 1998; Survase et al, 2007a; Fazenda et al, 2008; Seviour et al, 2011a). A quite relevant step consists in selecting an appropriate producing strain, whose preservation procedure should be assessed and standardized, and its production ability must be monitored over time (Fariña et al, 1996; Survase et al, 2006; Schmid, 2008).…”
Section: Reviewing the Knowledge And Advances On Scleroglucan Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in order to obtain high yields of a consistent polymer, it becomes essential to standardize a large-scale production process with a given strain under controlled conditions (Fariña et al, 1998; Survase et al, 2007a; Fazenda et al, 2008; Seviour et al, 2011a). A quite relevant step consists in selecting an appropriate producing strain, whose preservation procedure should be assessed and standardized, and its production ability must be monitored over time (Fariña et al, 1996; Survase et al, 2006; Schmid, 2008).…”
Section: Reviewing the Knowledge And Advances On Scleroglucan Productionmentioning
confidence: 99%
“…It was early suggested that a pelleted fungal morphology in Sclerotium sp. may produce higher β-glucan yields than diffuse mycelial cultures (Gibbs et al, 2000; Papagianni, 2004; Wucherpfennig et al, 2010; Schmid et al, 2011; Seviour et al, 2011a). Systematic studies on the relationship between aeration rate, mycelial morphology and EPS production were previously performed in Cordyceps militaris , finding that DO starvation at low airflow levels led to pellet autolysis and looser mycelial clumps.…”
Section: Reviewing the Knowledge And Advances On Scleroglucan Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP, NAD+); secondly, transcriptional regulation, where synthesis is tightly regulated and controlled by complex regulatory machinery, which functions when cells need to construct structural components like EPS that relate to pathogenicity and defense mechanisms; thirdly, in vivo biopolymerization, where there is a need for better characterization of polymerization enzymes (79) and the steps in EPS biosynthesis even though gene clusters have been known for several years (80); and finally, extracellular secretion, which poses process engineering challenges where titer is limited by viscosity leading to mass transfer issues (81). Host compatibility should also be considered, for example, the robustness of model organisms like E. coli to industrial conditions.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…Generally, typical microbial EPS fermentations start with the growth phase followed by the production phase (Toksoy Oner 2013). During the cultivations, severe changes in rheological properties of the microbial culture such as highly viscous and non-Newtonian broth may result in serious problems of mixing, heat transfer, oxygen supply, and also instabilities in the quality of the end product (Seviour et al 2011). Such challenges are encountered in the microbial production of pullulan (Cheng et al 2011) and xanthan (Palaniraj and Jayaraman 2011) but not in the production of low-viscosity polymers such as levan (K€ uç€ ukaşık et al 2011) or in high-temperature processes where thermophiles are utilized as microbial producers (Nicolaus et al 2010).…”
Section: Microbial Production Processesmentioning
confidence: 99%